SPIN: rapid synthesis, purification, and concentration of small drug-loaded liposomes. (2nd October 2018) - Roberts, Steven A.; Parikh, Neil; Blower, Ryan J.; Agrawal, Nitin
Abstract: Liposomes are one of the most studied nano-delivery systems. However, only a handful of formulations have received FDA approval. Existing liposome synthesis techniques are complex and specialized, posing a major impediment in design, implementation, and mass production of liposome delivery systems as therapeutic agents. Here, we demonstrate a unique 'synthesis and purification of injectable nanocarriers' (SPIN) technology for rapid and efficient production of small drug-loaded liposomes using common benchtop equipment. Unilamellar liposomes with mean diameter of 80 nm and polydispersity of 0.13 were synthesized without any secondary post-processing techniques. Encapsulation of dextrans (300–20, 000 Da) representing small and large molecular drug formulations was demonstrated without affecting the liposome characteristics. 99.9% of the non-encapsulated molecules were removed using a novel filter centrifugation technique, largely eliminating the need for tedious ultracentrifugation protocols. Finally, the functional efficacy of loaded liposomes as drug delivery vehicles was validated by encapsulating a fluorescent cell tracker (CMFDA) and observing the liposomal release and subsequent uptake of dye by metastatic breast cancer cells (MDA-MB-231) in vitro . The proposed simplified technique addresses the existing challenges associated with liposome preparation in resource limited settings and offers significant potential for advances in translational pharmaceutical development.